Perkawinan Poligami Menurut Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan dan Menurut Hukum Adat Desa Lamahelan Kecamatan Ile Boleng Kabupaten Flores Timur - Heribertus Virgi Golot; Agustinus Hedewata; Orpa J. Nubatonis (International Forum of Researchers and Lecturers, 2024)
The purpose of this study is to determine the requirements of polygamy according to Law Number 1 of 1974 concerning Marriage and according to the Customary Law of Lamahelan Village, Ile Boleng Subdistrict, East Flores Regency. To find out the legal consequences of polygamy according to Law Number 1 of 1974 concerning Marriage and according to the customary law of Lamahelan Village, Ile Boleng Subdistrict, East Flores Regency. This research was conducted using data collection techniques, namely, interviews and document studies. The data that has been collected both through interviews and document studies, examined one by one and arranged systematically so as to achieve the objectives of this research. The results of this study indicate that the requirements according to Law Number 1 of 1974 concerning Marriage and Menuut customary law of Lamahelan Village, Ile Boleng Subdistrict, East Flores Regency have similarities such as permission from husband or wife and so on. But there are several requirements from customary law that differ from the law, namely the dowry (belis). In addition, if a polygamous marriage according to Law Number 1 Year 1974 concerning Marriage is submitted to the court, then a polygamous marriage according to the customary law of Lamahelan Village, Ile Boleng Subdistrict, East Flores Regency is brought to the customary elders. For the legal consequences of polygamy according to Law No. 1 of 1974 concerning Marriage and according to the customary law of Lamahelan Village, Ile Boleng Subdistrict, East Flores Regency, both do not specifically regulate life after polygamy. Law Number 1 of 1974 concerning Marriage and the Customary Law of Lamahelan Village, Ile Boleng Subdistrict, East Flores Regency also both recognise that when polygamous, the responsibilities that arise will be greater because from previously supporting one family will become several families.